Archaeological research : a brief introduction - Peregrine, Peter N. (New York : Routledge, 2022)
"The third edition of Archaeological Research introduces the basic methods of archaeological re-search, including data collection, analysis, and interpretation, as well as considering the state of the field today. With new sections on curating archaeological collections and public archaeology, the third edition also adds a new chapter on the analysis of metals and glass. This popular, concise textbook exam-ines approaches to the archaeological record, sampling and research design, survey and excavation methods and strategies, recordkeeping, dating and analysis of archaeological materials, and the pro-fessional practice of archaeology. Archaeological Research continues to be an excellent text for undergraduate students in basic ar-chaeology courses, field methods courses, and field schools"--
Includes bibliographical references and index.
Keywords: Archaeology